Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Mahasiswa Manajemen Keuangan Syariah Pada Aplikasi Shopee - Hesti Asmana; H. Ahmad Syahrizal (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of price and product quality on the purchasing decisions of students in the Sharia Financial Management Study Program at UIN Sulthan Thaha Saifuddin Jambi. Price and product quality are two crucial factors that affect consumer behavior, particularly in the decision-making process. This research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to 78 active students as respondents. The data were analyzed using multiple linear regression to measure the influence of the independent variables (price and product quality) on the dependent variable (purchasing decision). The results show that both price and product quality have a positive and significant influence on students' purchasing decisions. These findings indicate that students tend to make purchases when the product price is affordable and the product quality meets their expectations